Tranexamic acid: Beware of anaesthetic misadventures - Sunanda Gupta; Anil K Bhiwal; Karuna Sharma (Wolters Kluwer Medknow Publications, 2018)
Tranexamic acid (TXA) is an antifibrinolytic agent that is commonly used in cardiac, gynecologic, and obstetric surgeries. Inadvertent intrathecal injection of the TXA may lead to serious side effects, including back pain, myoclonus, seizure, and ventricular fibrillation that can be attributed to similar appearance of ampoules, location of ampoules, and incorrect labeling of prefilled syringes and can be avoided by vigilance, correct labeling of syringes and ampoules, double checking medications prior to administration, and preventing manufacturing of vials of different drugs with similar appearance. Treatment of intrathecal injection of the TXA includes administration of the anticonvulsants, general anaesthetics, MgSO4, along with intensive haemodynamic monitoring, scalp electroencephalography monitoring guided burst suppression with thiopentone infusion and cerebrospinal fluid lavage.